Protocol to identify genes important for Candida albicans fitness in diverse environmental conditions using pooled bar-seq screening approach - Emily H. Xiong; Xiang Zhang; Nicole Robbins; Chad L. Myers; Leah E. Cowen (STAR Protocols, 2025)
Summary: Identifying genes important for fitness in Candida albicans advances our understanding of this important pathogen of humans. Here, we present a functional genomics approach for assessing fitness through the quantification of strain-specific barcodes. We describe steps for library preparation, propagation of strains, genomic DNA extraction, amplification of barcodes, and sequencing. We then detail the computational analysis of data to determine effect size and statistical significance.For complete details on the use and execution of this protocol, please refer to Xiong et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.